The genome sequence of Hirschfeldia incana, a new Brassicaceae model to improve photosynthetic light‐use efficiency. (7th November 2022) - Garassino, Francesco; Wijfjes, Raúl Y.; Boesten, René; Reyes Marquez, Francisca; Becker, Frank F. M.; Clapero, Vittoria; van den Hatert, Iris; Holmer, Rens; Schranz, M. Eric; Harbinson, Jeremy; de Ridder, Dick; Smit, Sandra; et al.
SUMMARY: Photosynthesis is a key process in sustaining plant and human life. Improving the photosynthetic capacity of agricultural crops is an attractive means to increase their yields. While the core mechanisms of photosynthesis are highly conserved in C3 plants, these mechanisms are very flexible, allowing considerable diversity in photosynthetic properties. Among this diversity is the maintenance of high photosynthetic light‐use efficiency at high irradiance as identified in a small number of exceptional C3 species. Hirschfeldia incana, a member of the Brassicaceae family, is such an exceptional species, and because it is easy to grow, it is an excellent model for studying the genetic and physiological basis of this trait. Here, we present a reference genome of H. incana and confirm its high photosynthetic light‐use efficiency. While H. incana has the highest photosynthetic rates found so far in the Brassicaceae, the light‐saturated assimilation rates of closely related Brassica rapa and Brassica nigra are also high. The H. incana genome has extensively diversified from that of B. rapa and B. nigra through large chromosomal rearrangements, species‐specific transposon activity, and differential retention of duplicated genes. Duplicated genes in H. incana, B. rapa, and B. nigra that are involved in photosynthesis and/or photoprotection show a positive correlation between copy number and gene expression, providing leads into the mechanisms underlying the high photosynthetic efficiency of these species. Our work demonstrates that the H. incana genome serves as a valuable resource for studying the evolution of high photosynthetic light‐use efficiency and enhancing photosynthetic rates in crop species. Significance Statement: Hirschfeldia incana is a diploid, wild species, closely related to Brassica crops, which displays remarkably high photosynthesis rates at high irradiance, a desirable trait to improve in crops to increase yield. We propose H. incana as an attractive high‐photosynthesis model species and present the reference genome sequence as a valuable resource for studying the evolution, genetics, and physiology of high photosynthetic light‐use efficiency at high irradiances.